Ethanol gas-phase ammoxidation to acetonitrile: the reactivity of supported vanadium oxide catalysts. Issue 1 (8th December 2016) - Folco, F.; Velasquez Ochoa, J.; Cavani, F.; Ott, L.; Janssen, M.
Abstract : The gas-phase ammoxidation of ethanol, a bio-based platform molecule, has been investigated as a possible more sustainable route for the production of acetonitrile, using supported vanadium oxide catalysts. The nature of the interaction between the support and the active species greatly affected the catalytic performance. Abstract : New insights on the gas-phase ammoxidation of ethanol to acetonitrile over supported vanadia catalysts were obtained by means of reactivity experiments (in ethanol ammoxidation and oxidation) as well as in situ Raman and DRIFT spectroscopy. It was found that the rate-determining step during the redox process depends on the support type. In the case of V2 O5 /ZrO2, the V oxidation state under reaction conditions is closer to V 5+, whereas with V2 O5 /TiO2, the reduction of V 5+ is faster than the re-oxidation of the corresponding reduced V species by O2 ; thus, the V oxidation state under steady state conditions is lower than for V2 O5 /ZrO2 . In the latter catalyst, the more oxidized V species is responsible for ammonia activation and reaction with the intermediate acetaldehyde, leading in the end to a better acetonitrile yield than with V2 O5 /TiO2 . It was also found that V2 O5 /ZrO2 is more selective to acetaldehyde than V2 O5 /TiO2 . With the former catalyst, ethanol is able to reduce V2 O5 only to a limited extent. Conversely, V2 O5 /TiO2 is readily reduced by ethanol but this reduced V species is responsible for an unselective oxidation of the alcohol, giving more CO and CO2 .